Potensi batuan sumber (source rock) hidrokarbon di Pegunungan Tigapuluh, Sumatera Tengah - Rachmat Heryanto; Heri Hermiyanto (Indonesian Journal on Geoscience, 2006)
http://dx.doi.org/10.17014/ijog.vol1no1.20065aThe Tigapuluh Mountain located in southeast corner of the Riau Province, is a part of the southern margin of the Central Sumatera Basin, one of the biggest hydrocarbon producing basin in Indonesia. The hydrocarbon source rock potential is a fine grained clastics within the Late Eocene Kelesa and Oligocene Lakat Formations. The Kelesa Formation source rock has a TOC value of 2.31–9.63%, with hydrocarbon content of a good to excellent categories (6.23–70.72 kg/ton rock), whereas the Lakat Formation has a TOC value of 0.67–3.46%, with hydrocarbon content of a poor to excellent categories (1.21–37.38 kg/ton rock). Source rock thermal maturation of the Kelesa Formation ranges from a late immature to early mature, with kerogen type of I and II, whereas the Lakat Formation ranges from a late immature, with kerogen type of I, II, and III. Diagenetic stage of the hydrocarbon source rock of the Kelesa Formation is included to Mudrock Stage II which is equivalent to a mesogenetic mature “A”. This diagenetic proccess was due to the burial history with the depth of up to 3000 m, resulted in a paleotemperature of 95C. The Lakat Formation is, however, included to Mudrock Stage I equivalent to the mesogenetic immature level. Burial history which occurred at the paleo temperature up to 65C, with the depth of burial up to 1500 m, led to the diagenetic process.